Method of manufacturing polarizing film

JP2023166877A5Pending Publication Date: 2025-01-10NITTO DENKO CORP
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2022077711
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2022-05-10
Publication Date
2025-01-10

AI Technical Summary

Technical Problem

Polarizing films in image display devices can affect display characteristics due to issues such as streaks, which are visible on the screen, particularly in displays with highly reflective metal layers like organic electroluminescent (OLED) and quantum dot (QLED) panels.

Method used

A method for manufacturing a polarizing film involves contacting a resin film containing iodine with a first liquid, typically an aqueous boric acid solution at elevated temperatures, followed by additional processing steps to achieve a polarizing film with reduced orientation and improved appearance, including stretching, dyeing, and drying processes to enhance optical properties.

Benefits of technology

The method results in a polarizing film with excellent appearance and improved display characteristics, reducing streaks and enhancing optical properties, suitable for use in various image display devices.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 00000000_0000_ABST
    Figure 00000000_0000_ABST
Patent Text Reader

Abstract

To provide a polarizing film which has superior appearance and may contribute to improvement in display characteristics of image display devices.SOLUTION: A method of manufacturing a polarizing film according to an embodiment of the present invention comprises bringing a resin film containing iodine and having a moisture content of 15 wt.% or less into contact with a first liquid. The first liquid is an aqueous solution of boric acid and iodine and is kept at a temperature of 60°C or higher.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical Field]

[0001] The present invention relates to a method for producing a polarizing film. [Background technology]

[0002] Liquid crystal display devices, a typical type of image display device, have polarizing films disposed on both sides of a liquid crystal cell due to their image formation method. Furthermore, with the spread of thin displays, displays equipped with organic electroluminescence (EL) panels (OLEDs) and displays using display panels made of inorganic light-emitting materials such as quantum dots (QLEDs) have been proposed. These panels have highly reflective metal layers, which can easily cause problems such as reflection of external light and glare of the background. It is known that these problems can be prevented by providing a circular polarizer, which has a polarizing film and a λ / 4 plate, on the viewing side (see, for example, Patent Documents 1 and 2). [Prior art documents] [Patent documents]

[0003] [Patent Document 1] Japanese Patent Application Laid-Open No. 2002-372622 [Patent Document 2] Patent No. 3325560 Summary of the Invention [Problem to be solved by the invention]

[0004] When a polarizing film is mounted on an image display device as described above, the appearance of the polarizing film may affect the display characteristics of the image display device. For example, if streaks occur on the polarizing film, the streaks may also be visible in the image display device.

[0005] The present invention has been made to solve the above problems, and a main object of the present invention is to provide a polarizing film that has an excellent appearance and can contribute to improving the display characteristics of image display devices. [Means for solving the problem]

[0006] 1. A method for producing a polarizing film according to an embodiment of the present invention includes contacting a resin film containing iodine and having a moisture content of 15% by weight or less with a first liquid, wherein the first liquid is an aqueous solution of boric acid and iodine, and the temperature of the first liquid is 60°C or higher. 2. In the manufacturing method described in 1 above, the resin film brought into contact with the first liquid may have a single-piece transmittance of 44% or more. 3. In the manufacturing method described in 1 or 2 above, the concentration of boric acid in the first liquid may be 3% by weight or more. 4. In the manufacturing method according to any one of the above 1 to 3, the iodine concentration of the first liquid may be 0.002% by weight to 0.01% by weight. 5. The manufacturing method according to any one of 1 to 4 above may include contacting the resin film, which has been in contact with the first liquid, with a second liquid. 6. In the manufacturing method described in 5 above, the second liquid may contain water. 7. In the manufacturing method according to any one of the above items 1 to 6, a polarizing film having a thickness of 22 μm or less may be obtained. [Effects of the Invention]

[0007] According to the present invention, a polarizing film having excellent appearance can be obtained. [Brief explanation of the drawings]

[0008] [Figure 1] 1 is a schematic cross-sectional view showing the general configuration of a laminate according to one embodiment of the present invention. [Figure 2] FIG. 1 is a schematic diagram showing an example of drying using a heating roll. [Figure 3] 1 is a schematic cross-sectional view showing the general configuration of a polarizing plate according to one embodiment of the present invention. [Figure 4] 1 is a representative view in the evaluation of appearance 1 (evaluation results of Comparative Example 5, Example 9, and Example 8). [Figure 5] 1 is a representative view in the evaluation of appearance 2 (evaluation results of Comparative Example 5, Example 9, and Example 8). DETAILED DESCRIPTION OF THE INVENTION

[0009] Hereinafter, embodiments of the present invention will be described, but the present invention is not limited to these embodiments.

[0010] (Definition of terms and symbols) The definitions of terms and symbols used in this specification are as follows. (1) Refractive index (nx, ny, nz) "nx" is the refractive index in the direction in which the in-plane refractive index is greatest (i.e., the slow axis direction), "ny" is the refractive index in the direction perpendicular to the slow axis in the plane (i.e., the fast axis direction), and "nz" is the refractive index in the thickness direction. (2) In-plane phase difference (Re) "Re(λ)" is the in-plane retardation measured with light of wavelength λ nm at 23°C. For example, "Re(550)" is the in-plane retardation measured with light of wavelength 550 nm at 23°C. Re(λ) is calculated by the formula: Re(λ)=(nx-ny)×d, where d (nm) is the thickness of the layer (film). (3) Retardation in the thickness direction (Rth) "Rth(λ)" is the retardation in the thickness direction measured with light of wavelength λ nm at 23°C. For example, "Rth(550)" is the retardation in the thickness direction measured with light of wavelength 550 nm at 23°C. Rth(λ) is calculated by the formula: Rth(λ) = (nx - nz) × d, where d (nm) is the thickness of the layer (film). (4) Nz coefficient The Nz coefficient is calculated by Nz=Rth / Re. (5)Angle When angles are referred to herein, the angles include both clockwise and counterclockwise angles relative to a reference direction, so for example, "45°" means ±45°.

[0011] A method for producing a polarizing film according to one embodiment of the present invention includes a first step of contacting a resin film containing iodine and having a predetermined moisture content with a first liquid, and may further include a second step of contacting the resin film with a second liquid after the first step.

[0012] A. Resin film production method The resin film can be obtained, for example, by forming a resin layer (typically, a polyvinyl alcohol-based resin layer) on a resin substrate, stretching the resulting laminate or resin film (typically, a polyvinyl alcohol-based resin film), dyeing the laminate with a dichroic substance (typically, iodine), and then drying the laminate. Hereinafter, the details of the method for producing the resin film will be described using a laminate as an example.

[0013] A-1.Laminate 1 is a schematic cross-sectional view showing the general configuration of a laminate according to one embodiment of the present invention. The laminate 1 has a thermoplastic resin substrate (e.g., a long piece) 2 and a polyvinyl alcohol (PVA)-based resin layer 3. Preferably, the laminate 1 is produced by forming the PVA-based resin layer 3 containing a PVA-based resin and a halide on the thermoplastic resin substrate 2. Specifically, the PVA-based resin layer 3 is formed by applying a coating liquid containing a PVA-based resin and a halide to the thermoplastic resin substrate 2 and drying it.

[0014] The thickness of the thermoplastic resin substrate is preferably 20 μm to 300 μm, more preferably 50 μm to 200 μm. If the thickness is less than 20 μm, it may be difficult to form a PVA-based resin layer. If the thickness is more than 300 μm, for example, in underwater stretching described below, it may take a long time for the thermoplastic resin substrate to absorb water, and an excessive load may be required for stretching.

[0015] The water absorption of the thermoplastic resin substrate is preferably 0.2% or more, and more preferably 0.3% or more. Such a thermoplastic resin substrate can absorb water, which acts as a plasticizer and plasticizes the substrate. As a result, the stretching stress can be significantly reduced, allowing for high stretching ratios. On the other hand, the water absorption of the thermoplastic resin substrate is preferably 3.0% or less, and more preferably 1.0% or less. This water absorption can prevent problems such as a significant decrease in the dimensional stability of the thermoplastic resin substrate during production, which can lead to poor quality of the resulting polarizing film. It can also prevent breakage of the thermoplastic resin substrate and peeling of the PVA-based resin layer during underwater stretching. The water absorption of the thermoplastic resin substrate can be adjusted, for example, by introducing a modifying group into the constituent materials. The water absorption is a value determined in accordance with JIS K 7209.

[0016] The glass transition temperature (Tg) of the thermoplastic resin substrate is preferably 120°C or lower. By using such a thermoplastic resin substrate, the stretchability of the laminate can be sufficiently ensured while suppressing crystallization of the PVA-based resin layer. Furthermore, considering the plasticization of the thermoplastic resin substrate with water and the smooth underwater stretching, the Tg is more preferably 100°C or lower, and even more preferably 90°C or lower. On the other hand, the Tg of the thermoplastic resin substrate is preferably 60°C or higher. Such a Tg prevents problems such as deformation of the thermoplastic resin substrate (e.g., the occurrence of unevenness, sagging, wrinkles, etc.) during the application and drying of the coating liquid, allowing for the production of a satisfactory laminate. Furthermore, the resin layer can be satisfactorily stretched at a suitable temperature (e.g., about 60°C). The Tg of the thermoplastic resin substrate can be adjusted, for example, by introducing a modifying group into the constituent material or by heating using a crystallizing material. The glass transition temperature (Tg) is a value determined in accordance with JIS K 7121.

[0017] Any suitable thermoplastic resin can be used as the constituent material of the thermoplastic resin substrate. Examples of the thermoplastic resin include ester-based resins such as polyethylene terephthalate-based resins, cycloolefin-based resins such as norbornene-based resins, olefin-based resins such as polypropylene, polyamide-based resins, polycarbonate-based resins, and copolymer resins thereof. Among these, norbornene-based resins and amorphous polyethylene terephthalate-based resins are preferred.

[0018] In one embodiment, amorphous (non-crystallized) polyethylene terephthalate resins are preferably used. Among them, amorphous (hard to crystallize) polyethylene terephthalate resins are particularly preferably used. Specific examples of amorphous polyethylene terephthalate resins include copolymers further containing isophthalic acid and / or cyclohexanedicarboxylic acid as dicarboxylic acids, and copolymers further containing cyclohexanedimethanol or diethylene glycol as glycols.

[0019] In another embodiment, a polyethylene terephthalate resin having an isophthalic acid unit is preferably used. This is because it has extremely excellent stretchability and can suppress crystallization during stretching. This is thought to be because the introduction of the isophthalic acid unit imparts a large curvature to the main chain. The polyethylene terephthalate resin has a terephthalic acid unit and an ethylene glycol unit. The content of the isophthalic acid unit is preferably 0.1 mol% or more, more preferably 1.0 mol% or more, based on the total of all repeating units. This is because a thermoplastic resin substrate with extremely excellent stretchability can be obtained. On the other hand, the content of the isophthalic acid unit is preferably 20 mol% or less, more preferably 10 mol% or less, based on the total of all repeating units. This is because it can satisfactorily increase the crystallinity during drying, as described below.

[0020] The thermoplastic resin substrate may be stretched in advance (for example, before forming the PVA-based resin layer). In one embodiment, the long thermoplastic resin substrate is stretched in the transverse direction. The transverse direction is preferably a direction perpendicular to the stretching direction of the laminate described below. In this specification, "perpendicular" also includes a case where the direction is substantially perpendicular. Here, "substantially perpendicular" includes a case where the direction is 90°±5.0°, preferably 90°±3.0°, and more preferably 90°±1.0°. The stretching temperature of the thermoplastic resin substrate is preferably Tg-10°C to Tg+50°C relative to the glass transition temperature (Tg) of the thermoplastic resin substrate. The stretching ratio of the thermoplastic resin substrate is preferably 1.5 times to 3.0 times. Any appropriate method can be used to stretch the thermoplastic resin substrate. Specifically, either fixed-end stretching or free-end stretching may be used. The stretching method may be a dry method or a wet method. The stretching may be carried out in one stage or in multiple stages. When the stretching is carried out in multiple stages, the stretching ratio is the product of the stretching ratios in each stage.

[0021] The coating liquid is typically a solution in which a PVA resin and a halide are dissolved in a solvent. Examples of solvents include water, dimethyl sulfoxide, dimethylformamide, dimethylacetamide, N-methylpyrrolidone, various glycols, polyhydric alcohols such as trimethylolpropane, and amines such as ethylenediamine and diethylenetriamine. These can be used alone or in combination. Of these, water is preferred. The content of the PVA resin in the coating liquid is preferably 3 to 20 parts by weight per 100 parts by weight of the solvent. This range allows the formation of a uniform coating film that adheres closely to the thermoplastic resin substrate. The content of the halide in the coating liquid is preferably 5 to 20 parts by weight per 100 parts by weight of the PVA resin.

[0022] Examples of the PVA resin include polyvinyl alcohol and ethylene-vinyl alcohol copolymer. Polyvinyl alcohol is obtained by saponifying polyvinyl acetate. Ethylene-vinyl alcohol copolymer is obtained by saponifying ethylene-vinyl acetate copolymer. The saponification degree of the PVA resin is usually 85 mol % to 100 mol %, preferably 95.0 mol % to 99.95 mol %, and more preferably 99.0 mol % to 99.93 mol %. By using a PVA resin with such a saponification degree, a polarizing film with excellent durability can be obtained. If the saponification degree is too high, gelation may occur. The saponification degree can be determined in accordance with JIS K 6726-1994.

[0023] The average degree of polymerization of the PVA resin is usually 1000 to 10000, preferably 1200 to 4500, and more preferably 1500 to 4300. The average degree of polymerization can be determined in accordance with JIS K 6726-1994.

[0024] Any appropriate halide can be used as the halide. Examples include iodides such as potassium iodide, sodium iodide, and lithium iodide, and chlorides such as sodium chloride. Among these, potassium iodide is preferred. The use of a halide can produce a polarizing film with excellent optical properties. Specifically, crystallization of the PVA-based resin after the auxiliary air-stretching described below is promoted, and disturbance of the orientation and deterioration of the orientation of polyvinyl alcohol molecules during subsequent wet treatments (e.g., dyeing and water-stretching described below) can be suppressed, resulting in a polarizing film with excellent optical properties.

[0025] In preparing the coating solution, the halide is preferably blended in an amount of 5 to 20 parts by weight, more preferably 10 to 15 parts by weight, per 100 parts by weight of the PVA-based resin. Specifically, the content of the halide in the resulting PVA-based resin layer is preferably 5 to 20 parts by weight, more preferably 10 to 15 parts by weight, per 100 parts by weight of the PVA-based resin. If the amount of halide relative to the PVA-based resin is too high, for example, the halide may bleed out, causing the resulting polarizing film to become cloudy.

[0026] Additives may be blended into the coating solution. Examples of additives include plasticizers and surfactants. Examples of plasticizers include polyhydric alcohols such as ethylene glycol and glycerin. Examples of surfactants include nonionic surfactants. These are used, for example, to improve the uniformity, dyeability, and stretchability of the resulting PVA-based resin layer.

[0027] Examples of methods for applying the coating liquid include roll coating, spin coating, wire bar coating, dip coating, die coating, curtain coating, spray coating, and knife coating (comma coating, etc.). The temperature for applying and drying the coating liquid is preferably 50°C or higher.

[0028] The thickness of the PVA resin layer is preferably 3 μm to 40 μm, and more preferably 3 μm to 20 μm.

[0029] Before forming the PVA-based resin layer, the thermoplastic resin substrate may be subjected to a surface treatment (e.g., corona treatment, etc.), or an easy-adhesion layer may be formed on the thermoplastic resin substrate. By performing such treatment, the adhesion between the thermoplastic resin substrate and the PVA-based resin layer can be improved.

[0030] A-2.Stretching The stretching is preferably performed by dry stretching (in-air auxiliary stretching) of the laminate followed by underwater stretching. Auxiliary stretching allows stretching while suppressing crystallization of the thermoplastic resin substrate, thereby solving the problem of reduced stretchability due to excessive crystallization of the thermoplastic resin substrate during stretching in boric acid water, and allows the laminate to be stretched at a higher stretching ratio. Furthermore, when a thermoplastic resin substrate is used, the coating temperature may be set low, which can lead to a problem of relatively low crystallization of the PVA-based resin, resulting in insufficient optical properties. In contrast, auxiliary stretching can enhance the crystallinity of the PVA-based resin, even when a thermoplastic resin is used. Furthermore, by enhancing the orientation of the PVA-based resin in advance, problems such as reduced orientation and dissolution of the PVA-based resin during subsequent wet processing can be prevented. This allows for a polarizing film with excellent optical properties to be obtained.

[0031] The method of the auxiliary in-air stretching may be fixed-end stretching (e.g., stretching using a tenter stretching machine) or free-end stretching (e.g., uniaxial stretching by passing the laminate between rolls with different peripheral speeds). Free-end stretching is preferably used. For example, heated roll stretching is used, in which the laminate is stretched by the difference in peripheral speed between heated rolls while being transported in its longitudinal direction. In one embodiment, the auxiliary in-air stretching includes a zone stretching step in a heated space (zone) and a heated roll stretching step. The order of the zone stretching step and the heated roll stretching step is not limited, but for example, the zone stretching step and the heated roll stretching step are performed in this order. In another embodiment, the film is stretched by gripping the edges of the film in a tenter stretching machine and widening the distance between the tenters in the machine direction (the widening of the distance between the tenters corresponds to the stretch ratio). In this case, the distance between the tenters in the width direction (perpendicular to the machine direction) is preferably set so that it is closer to the free-end stretching ratio in the machine direction. In the case of free-end stretching, the shrinkage ratio in the width direction is calculated by the formula: shrinkage ratio in the width direction = (1 / stretching ratio) 1 / 2 It is calculated as follows.

[0032] The draw ratio of the auxiliary in-air stretching is preferably 2.0 to 3.5. The auxiliary in-air stretching may be carried out in one stage or in multiple stages. When carried out in multiple stages, the draw ratio is the product of the draw ratios in each stage. The stretching direction in the auxiliary in-air stretching is preferably approximately the same as the stretching direction in underwater stretching described below.

[0033] The stretching temperature for the auxiliary in-air stretching is set to any appropriate value depending on, for example, the thermoplastic resin substrate and the stretching method used. The stretching temperature is preferably equal to or higher than the glass transition temperature (Tg) of the thermoplastic resin substrate, more preferably equal to or higher than Tg + 10°C, and even more preferably equal to or higher than Tg + 15°C. On the other hand, the upper limit of the stretching temperature is preferably 170°C. By stretching at such a temperature, rapid crystallization of the PVA-based resin can be suppressed, and problems caused by the crystallization (for example, interference with the orientation of the PVA-based resin layer due to stretching) can be suppressed.

[0034] The underwater stretching is typically performed by immersing the laminate in a stretching bath. Underwater stretching allows stretching to be performed at a temperature lower than the glass transition temperature (typically about 80°C) of the thermoplastic resin substrate or the PVA-based resin layer, and the PVA-based resin layer can be stretched at a high magnification while suppressing crystallization. As a result, a polarizing film with excellent optical properties can be obtained.

[0035] The underwater stretching method may be fixed-end stretching or free-end stretching (for example, a method in which the laminate is passed between rolls with different peripheral speeds for uniaxial stretching). Free-end stretching is preferably used. The stretching of the laminate may be carried out in one stage or in multiple stages. When stretching is carried out in multiple stages, the stretch ratio of the laminate described below is the product of the stretch ratios in each stage.

[0036] The underwater stretching is preferably performed by immersing the laminate in an aqueous boric acid solution (stretching in boric acid solution). Using an aqueous boric acid solution as the stretching bath can impart to the PVA-based resin layer rigidity sufficient to withstand the tension applied during stretching and water resistance sufficient to prevent dissolution in water. Specifically, boric acid generates tetrahydroxyborate anions in the aqueous solution, which can crosslink with the PVA-based resin through hydrogen bonding. As a result, the PVA-based resin layer is imparted with rigidity and water resistance, allowing it to be stretched satisfactorily, resulting in a polarizing film with excellent optical properties.

[0037] The boric acid aqueous solution is preferably obtained by dissolving boric acid and / or a borate in water as a solvent. The boric acid concentration is preferably 1 to 10 parts by weight, more preferably 2.5 to 6 parts by weight, and even more preferably 3 to 5 parts by weight, per 100 parts by weight of water. By adjusting the boric acid concentration to 1 part by weight or more, dissolution of the PVA-based resin layer can be effectively suppressed, allowing for the production of a polarizing film with better properties. In addition to boric acid or a borate, aqueous solutions obtained by dissolving boron compounds such as borax, glyoxal, glutaraldehyde, etc. in a solvent can also be used.

[0038] Preferably, an iodide is added to the drawing bath (boric acid aqueous solution). Adding an iodide can prevent iodine adsorbed in the PVA resin layer from leaching out. Examples of iodides include potassium iodide, lithium iodide, sodium iodide, zinc iodide, aluminum iodide, lead iodide, copper iodide, barium iodide, calcium iodide, tin iodide, and titanium iodide. The concentration of the iodide is preferably 0.05 to 15 parts by weight, more preferably 0.5 to 8 parts by weight, per 100 parts by weight of water.

[0039] The stretching temperature (liquid temperature of the stretching bath) is preferably 40°C or higher, more preferably 60°C or higher. At such a temperature, the film can be stretched at a high ratio while suppressing dissolution of the PVA-based resin layer. Specifically, as described above, the glass transition temperature (Tg) of the thermoplastic resin substrate is preferably 60°C or higher in relation to the formation of the PVA-based resin layer. In this case, if the stretching temperature is lower than 40°C, good stretching may not be possible, even taking into account the plasticization of the thermoplastic resin substrate by water. On the other hand, the stretching temperature is, for example, 70°C or lower, preferably 67°C or lower, and more preferably 65°C or lower. The higher the stretching temperature, the higher the solubility of the PVA-based resin layer, which may result in poor optical properties. The immersion time of the laminate in the stretching bath is preferably 15 seconds to 5 minutes.

[0040] The stretching ratio in underwater stretching is preferably 1.5 times or more, and more preferably 3.0 times or more. The total stretching ratio of the laminate (stretching ratio obtained by combining the auxiliary in-air stretching and underwater stretching) is preferably 5.0 times or more, more preferably 5.5 times or more, and even more preferably 6.0 times or more, relative to the original length of the laminate. By achieving such a high stretching ratio, a polarizing film with extremely excellent optical properties can be produced. Such a high stretching ratio can be achieved by employing underwater stretching (stretching in boric acid water).

[0041] A-3. Dyeing The dyeing is typically carried out by adsorbing iodine to the PVA-based resin layer. Examples of methods for adsorbing iodine include immersing the PVA-based resin layer (laminate) in a dyeing solution containing iodine, applying the dyeing solution to the PVA-based resin layer, and spraying the dyeing solution onto the PVA-based resin layer. The preferred method is immersing the laminate in a dyeing solution (dye bath), as this allows for good adsorption of iodine.

[0042] The dyeing solution is preferably an aqueous iodine solution. The amount of iodine blended is preferably 0.05 to 0.5 parts by weight per 100 parts by weight of water. To increase the solubility of iodine in water, it is preferable to blend an iodide into the aqueous iodine solution. Specific examples of iodide are as described above. Potassium iodide is preferably used. The amount of iodide blended is preferably 0.1 to 10 parts by weight, more preferably 0.3 to 5 parts by weight, per 100 parts by weight of water. The temperature of the dyeing solution during dyeing is preferably 20°C to 50°C to suppress dissolution of the PVA-based resin. When the PVA-based resin layer is immersed in the dyeing solution, the immersion time is preferably 5 seconds to 5 minutes, more preferably 30 to 90 seconds, to ensure the transmittance of the PVA-based resin layer.

[0043] The dyeing conditions (concentration, liquid temperature, immersion time) can be set so that the resulting resin film has a single transmittance of 42% or more and a polarization degree of 85% or more. For example, the dyeing conditions are such that the ratio of the iodine content to the potassium iodide content in the iodine aqueous solution, which is the dyeing solution, is preferably 1:5 to 1:20, more preferably 1:5 to 1:10.

[0044] When dyeing is performed immediately after immersing a laminate in a treatment bath containing boric acid (for example, an insolubilization treatment described below), the boric acid may be mixed into the dye bath, changing the boric acid concentration in the dye bath and causing instability in the dyeability. To prevent this instability in the dyeability, the boric acid concentration in the dye bath is adjusted to preferably 4 parts by weight or less, more preferably 2 parts by weight or less, per 100 parts by weight of water. On the other hand, the boric acid concentration in the dye bath is preferably 0.1 parts by weight or more, more preferably 0.2 parts by weight or more, and even more preferably 0.5 parts by weight or more, per 100 parts by weight of water. In one embodiment, dyeing is performed using a dye bath that contains boric acid in advance. This embodiment can reduce the rate of change in boric acid concentration when boric acid is mixed into the dye bath. The amount of boric acid to be added to the dye bath in advance (the content of boric acid not derived from the treatment bath) is preferably 0.1 to 2 parts by weight, and more preferably 0.5 to 1.5 parts by weight, per 100 parts by weight of water.

[0045] A-4. Other processing If necessary, after the above-mentioned auxiliary air-stretching, an insolubilization treatment is carried out before underwater stretching and dyeing. The insolubilization treatment is typically carried out by immersing the PVA-based resin layer in an aqueous boric acid solution. By carrying out the insolubilization treatment, water resistance is imparted to the PVA-based resin layer, and it is possible to prevent a decrease in the orientation of PVA when immersed in water. The concentration of the aqueous boric acid solution in the insolubilization treatment is preferably 1 to 4 parts by weight per 100 parts by weight of water. The temperature of the insolubilization treatment (liquid temperature of the aqueous boric acid solution) is preferably 20 to 50°C.

[0046] If necessary, a crosslinking treatment is carried out after dyeing and before underwater stretching. The crosslinking treatment is typically carried out by immersing the PVA-based resin layer in an aqueous boric acid solution. The crosslinking treatment imparts water resistance to the PVA-based resin layer, thereby preventing a decrease in the orientation of the PVA during the subsequent underwater stretching. The concentration of the aqueous boric acid solution in the crosslinking treatment is preferably 1 to 5 parts by weight per 100 parts by weight of water. It is preferable to add an iodide to the aqueous boric acid solution. Adding an iodide can suppress the elution of iodine adsorbed to the PVA-based resin layer. Specific examples of iodides are as described above. The amount of iodide added is preferably 1 to 5 parts by weight per 100 parts by weight of water. The temperature of the crosslinking treatment (liquid temperature of the aqueous boric acid solution) is preferably 20°C to 50°C.

[0047] Preferably, after the underwater stretching, washing is carried out before the drying described below. Washing is typically carried out by immersing the PVA-based resin layer in an aqueous potassium iodide solution.

[0048] A-5.Drying The drying can be performed by any appropriate method and under any appropriate conditions. Specifically, the drying can be performed by heating the entire zone (zone heating method) or by heating the transport rolls (heating roll method). The heating roll method is preferably used, and more preferably both. The use of a heating roll efficiently suppresses heat curling of the laminate, resulting in the production of a high-quality polarizing film. Specifically, drying the laminate while it is aligned with the heating roll efficiently promotes crystallization of the thermoplastic resin substrate, thereby increasing the crystallinity. Even at a relatively low drying temperature, the crystallinity of the thermoplastic resin substrate can be effectively increased. As a result, the rigidity of the thermoplastic resin substrate increases, enabling it to withstand shrinkage of the PVA-based resin layer due to drying, thereby suppressing curling. Furthermore, the use of a heating roll allows the laminate to be dried while remaining flat, thereby suppressing not only curling but also wrinkling.

[0049] Drying can shrink the laminate in the width direction, improving its optical properties. This is because it can effectively increase the orientation of the PVA and the PVA / iodine complex. The shrinkage rate of the laminate in the width direction due to drying is preferably 1% to 10%, more preferably 2% to 8%, and even more preferably 4% to 6%. By using a heated roll, the laminate can be continuously shrunk in the width direction while being transported, achieving high productivity.

[0050] 2 is a schematic diagram showing an example of drying using heated rolls. In the illustrated example, the laminate 200 is dried while being transported by transport rolls R1 to R6 heated to a predetermined temperature and guide rolls G1 to G4. In the illustrated example, the transport rolls R1 to R6 are arranged so as to alternately and continuously heat the surface of the PVA resin layer and the surface of the thermoplastic resin substrate, but the transport rolls R1 to R6 may also be arranged so as to continuously heat only one surface of the laminate 200 (for example, the thermoplastic resin substrate surface).

[0051] Drying conditions can be controlled by adjusting the heating temperature of the transport rolls (heating roll temperature), the number of heating rolls, the contact time with the heating rolls, etc. The temperature of the heating rolls is preferably 60°C to 120°C, more preferably 65°C to 100°C, and even more preferably 70°C to 80°C. At such temperatures, the crystallization degree of the thermoplastic resin can be increased to suppress curling, and the laminate can be endowed with extremely excellent durability. The temperature of the heating rolls can be measured with a contact thermometer. In the illustrated example, six transport rolls are provided, but there is no particular limitation as long as there are multiple transport rolls. The number of transport rolls is usually 2 to 40, preferably 4 to 30. The contact time between the laminate and the heating rolls (total contact time) is preferably 1 to 300 seconds, more preferably 1 to 20 seconds, and even more preferably 1 to 10 seconds.

[0052] The heating rolls may be installed in a heating furnace (e.g., an oven) or in a normal production line (under room temperature). Preferably, they are installed in a heating furnace equipped with a blower. By using both heating roll drying and hot air drying, it is possible to suppress abrupt temperature changes between the heating rolls, and to easily control shrinkage in the width direction. The hot air drying temperature is preferably 30°C to 100°C. The hot air drying time is preferably 1 second to 300 seconds. The hot air speed is preferably about 10 m / s to 30 m / s. Note that this air speed is the air speed inside the heating furnace and can be measured with a mini-vane type digital anemometer.

[0053] A-6.Resin film The moisture content of the resin film to be subjected to the first step described below is, for example, 15% by weight or less, preferably 12% by weight or less, more preferably 9% by weight or less, and even more preferably 6% by weight or less. On the other hand, the moisture content of the resin film is, for example, 3% by weight or more. The resin film that has been dried as described above can satisfy such a moisture content.

[0054] The resin film to be subjected to the first step described below preferably exhibits absorption dichroism at any wavelength between 380 nm and 780 nm. The resin film has a single transmittance (Ts) of, for example, 42% or more, preferably 44% or more. The higher the transmittance, the more easily streaks tend to be visible. On the other hand, the resin film has a single transmittance (Ts) of, for example, 49% or less.

[0055] The polarization degree (P) of the resin film to be subjected to the first step described below is, for example, 85% or more, preferably 90% or more, more preferably 95% or more, and even more preferably 98% or more. On the other hand, the polarization degree of the resin film is, for example, 99.996% or less.

[0056] The single transmittance is typically a Y value measured using an ultraviolet-visible spectrophotometer and corrected for visibility. The polarization degree is typically calculated using the following formula based on the parallel transmittance Tp and crossed transmittance Tc measured using an ultraviolet-visible spectrophotometer and corrected for visibility. Degree of polarization (%)={(Tp-Tc) / (Tp+Tc)} 1 / 2 ×100

[0057] The orientation of the resin film (PVA orientation) to be subjected to the first step described below is, for example, 0.20 or more, preferably 0.25 or more, and more preferably 0.30 or more, while the orientation of the resin film (PVA orientation) is, for example, 0.40 or less.

[0058] The orientation can be determined by measuring the spectrum of the resin film (polarizing film) by the ATR method using a Fourier transform infrared spectrometer (for example, a model "Frontier FT-IR" manufactured by PerkinElmer) and calculating the orientation of the PVA from the spectrum obtained. Specifically, the spectrum of the resin film (polarizing film) is measured at 0° and 90° polarized light incidence, and the 2940 cm due to -OH is calculated. -1 and 3300 cm -1 Peak intensity ratio a(I 2940 / I 3330 ) is calculated. Then, the dichroic ratio is calculated as the ratio b (a 0° / a 90° ) and calculate the index of orientation, c = (1 - b) / [(2 b + 1) × (-2)]. Here, the higher the value of c, the higher the orientation of the PVA.

[0059] The thickness of the resin film to be subjected to the first step described below is, for example, 22 μm or less, and may be 16 μm or less, 12 μm or less, 8 μm or less, or 6 μm or less. On the other hand, the thickness of the resin film is preferably 1 μm or more, and more preferably 2 μm or more.

[0060] B-1.First step As described above, in the first step, the resin film is brought into contact with the first liquid. Preferably, the resin film is immersed in the first liquid. When the resin film is immersed in the first liquid, one side of the resin film may be supported (protected) by any appropriate support substrate. In one embodiment, the resin substrate is used as the support substrate. Specifically, the resin film is immersed in the first liquid without peeling the resin substrate from the resin film (in the form of the laminate). In another embodiment, a protective layer, which will be described later, is used as the support substrate. For example, after a protective layer is laminated on the surface of the resin film of the laminate, the resin substrate is peeled from the resin film to produce a laminate of the protective layer and the resin film, and this laminate is immersed in the first liquid. When immersed in the first liquid, the resin film may be in the form of a long sheet or a sheet.

[0061] By contacting the first liquid, a polarizing film with excellent appearance can be obtained. Specifically, by contacting the first liquid, the orientation of the resin film (orientation of PVA) decreases, and components originally contained in the resin film (e.g., borate ions, iodine ions) enter and exit the resin film, which can eliminate streaks that have appeared in the resin film. The difference in the orientation of the resin film (orientation of PVA) before and after contact with the first liquid is, for example, 0.05 to 0.2. The orientation of the resin film (orientation of PVA) after contact with the first liquid is, for example, 0.10 to 0.30.

[0062] The resin film's simplex transmittance (Ts) can be increased by contacting with the first liquid. The difference in the resin film's simplex transmittance (Ts) before and after contact with the first liquid is preferably 1.5% or more, more preferably 3% or more, and may be 5% or more, or even 7% or more. On the other hand, the difference in the resin film's simplex transmittance (Ts) before and after contact with the first liquid is preferably 10% or less. The resin film's simplex transmittance (Ts) after contact with the first liquid is, for example, 45% or more, preferably 47% or more. On the other hand, the resin film's simplex transmittance (Ts) after contact with the first liquid is preferably 55% or less.

[0063] The degree of polarization (P) of the resin film can decrease when it is brought into contact with the first liquid. The difference in the degree of polarization (P) of the resin film before and after contact with the first liquid is, for example, 10% to 20%. The degree of polarization (P) of the resin film after contact with the first liquid is, for example, 65% to 97%.

[0064] The temperature of the first liquid when brought into contact with the resin film is, for example, 60°C or higher, or may be 65°C or higher, 70°C or higher, or 75°C or higher. By using a first liquid at such a temperature, for example, the orientation of the resin film (orientation of PVA) can be reduced. On the other hand, the temperature of the first liquid is, for example, 90°C or lower, preferably 85°C or lower.

[0065] The immersion time (contact time) in the first liquid is set depending on, for example, the temperature of the first liquid, the thickness of the resin film, the concentration of the components contained in the first liquid, etc. The immersion time in the first liquid is, for example, 1 to 60 minutes, and preferably 2 to 30 minutes.

[0066] A boric acid aqueous solution is preferably used as the first liquid. The use of a boric acid aqueous solution can effectively reduce the orientation of the resin film (PVA orientation). For example, even if the temperature of the first liquid is increased (e.g., 60°C or higher), the orientation of the PVA can be reduced (the PVA chains can be loosened) without dissolving the resin film in the first liquid, and the PVA can be re-crosslinked and homogenized by the inflow and outflow of boric acid ions. The concentration of the boric acid aqueous solution is preferably 3% by weight or more, more preferably 4% by weight or more. From the viewpoint of the solubility of boric acid, the concentration of the boric acid aqueous solution is, for example, 8% by weight or less.

[0067] The first liquid preferably contains iodine. The inclusion of iodine can promote the ingress and egress of components originally contained in the resin film. The concentration of iodine in the first liquid is preferably 0.002 wt % or more. On the other hand, the concentration of iodine in the first liquid is preferably 0.01 wt % or less, more preferably 0.005 wt % or less. Such a concentration can prevent dyeing of the resin film from taking priority over the ingress and egress of components originally contained in the resin film.

[0068] The first liquid may contain an iodide such as potassium iodide, for example, in order to improve the solubility of iodine. The concentration of the iodide is, for example, 0.007% by weight to 1% by weight.

[0069] B-2.Second process As described above, in the second step, the resin film is brought into contact with the second liquid. Typically, the resin film is immersed in the second liquid. As in the first step, when the resin film is immersed in the second liquid, one side of the resin film is preferably supported (protected) by any appropriate support substrate. Details are as described above. By contacting the resin film with the second liquid, the resin film can be cleaned (for example, by cleaning with boric acid). Furthermore, by contacting the resin film with the second liquid, the hue of the resulting polarizing film can be adjusted.

[0070] Contact with the second liquid can reduce the single transmittance (Ts) of the resin film. In one embodiment, the treatment conditions with the second liquid are adjusted depending on the desired optical properties (e.g., single transmittance, polarization degree) of the resulting polarizing film. The difference in the single transmittance (Ts) of the resin film before and after contact with the second liquid is, for example, 0.1% to 10%. The single transmittance (Ts) of the resin film after contact with the second liquid corresponds to the single transmittance (Ts) of the polarizing film described below.

[0071] The degree of polarization (P) of the resin film can be increased by contacting it with the second liquid. The difference in the degree of polarization (P) of the resin film before and after contacting it with the second liquid is, for example, 0.1% to 20%. The degree of polarization (P) of the resin film after contacting it with the second liquid corresponds to the degree of polarization (P) of the polarizing film described below.

[0072] The orientation of the resin film (orientation of PVA) can be increased by contacting with the second liquid. The difference in the orientation of the resin film (orientation of PVA) before and after contact with the second liquid is, for example, 0.01 to 0.10. The orientation of the resin film (orientation of PVA) after contact with the second liquid is, for example, 0.15 to 0.35.

[0073] The temperature of the second liquid when it is brought into contact with the resin film is typically set to room temperature, for example, 15° C. to 40° C. The immersion time (contact time) in the second liquid is, for example, 1 second to 1 minute.

[0074] The second liquid typically contains an aqueous solvent (preferably water). The second liquid may contain an iodide such as potassium iodide. By containing an iodide, the blue tint of the resulting polarizing film can be suppressed. The concentration of iodide in the iodide second liquid is, for example, 0% by weight to 6% by weight.

[0075] B-3. ​​Other processes The resin film (polarizing film) that has been subjected to the second step can be dried at a drying temperature of, for example, 30° C. to 60° C. The drying time is, for example, 15 seconds to 3 minutes.

[0076] C. Polarizing film The polarizing film obtained by the manufacturing method according to the embodiment of the present invention can exhibit absorption dichroism at any wavelength between 380 nm and 780 nm. The single transmittance (Ts) of the polarizing film is preferably 42% or more, and may be 44% or more, or 46% or more. Such a transmittance can contribute to reducing the power consumption of the image display device in which it is installed. The manufacturing method according to the embodiment of the present invention can obtain a polarizing film that combines high transmittance and excellent appearance. Meanwhile, the single transmittance (Ts) of the polarizing film is, for example, 55% or less, and may be 50% or less, or 48% or less.

[0077] The polarization degree (P) of the polarizing film is, for example, 70% or more, preferably 75% or more, and more preferably 85% or more, while the polarization degree of the polarizing film is, for example, 98% or less.

[0078] The orientation of the polarizing film (orientation of PVA) is preferably 0.20 or more, more preferably 0.25 or more, while the orientation of the resin film (orientation of PVA) is, for example, 0.35 or less.

[0079] The thickness of the polarizing film is, for example, 22 μm or less, or may be 16 μm or less, 12 μm or less, 8 μm or less, or 6 μm or less, while the thickness of the polarizing film is preferably 1 μm or more, and more preferably 2 μm or more.

[0080] D. Polarizing plate A polarizing plate according to one embodiment of the present invention has the above polarizing film and a protective layer or a retardation layer disposed on at least one side of the polarizing film.

[0081] 3 is a schematic cross-sectional view showing the general configuration of a polarizing plate according to one embodiment of the present invention. A polarizing plate (polarizing plate with a retardation layer) 100 includes a polarizing film 10 having a first main surface 10a and a second main surface 10b facing each other, a protective layer 20 disposed on the first main surface 10a side (e.g., the viewing side) of the polarizing film 10, and a retardation layer 30 and a pressure-sensitive adhesive layer 40 disposed on the second main surface 10b side of the polarizing film 10. The retardation layer 30 may be a single layer or may have a laminate structure in which two or more layers are laminated. A second protective layer may be disposed between the polarizing film 10 and the retardation layer 30.

[0082] Although not shown, the polarizing plate may further include other functional layers. The type, characteristics, number, combination, arrangement, etc. of the functional layers that the polarizing plate may have may be appropriately set depending on the purpose. For example, the polarizing plate may further include a conductive layer or an isotropic substrate with a conductive layer. A polarizing plate having a conductive layer or an isotropic substrate with a conductive layer (polarizing plate with a retardation layer) is applied to, for example, a so-called inner touch panel type input display device in which a touch sensor is incorporated inside an image display panel. As another example, the polarizing plate may further include other retardation layers. The optical properties (e.g., refractive index characteristics, in-plane retardation, Nz coefficient, photoelastic coefficient), thickness, arrangement, etc. of the other retardation layers may be appropriately set depending on the purpose. As a specific example, the viewing side of the polarizing film 10 may be provided with other retardation layers (typically, a layer imparting (elliptically) circular polarization function or a layer imparting ultra-high retardation) to improve visibility when viewed through polarized sunglasses. By including such a layer, excellent visibility can be achieved even when the display screen is viewed through polarized lenses such as polarized sunglasses, etc. Therefore, the obtained polarizing plate (polarizing plate with a retardation layer) can be suitably applied to image display devices that can be used outdoors.

[0083] Each member constituting the polarizing plate may be laminated via any appropriate adhesive layer (not shown). Specific examples of the adhesive layer include an adhesive layer and a pressure-sensitive adhesive layer. Specifically, the retardation layer 30 may be attached to the polarizing film 10 or the second protective layer via an adhesive layer (preferably using an active energy ray-curable adhesive), or may be attached to the polarizing film 10 or the second protective layer via a pressure-sensitive adhesive layer. When the retardation layer 30 has a laminate structure of two or more layers, the respective retardation layers are attached to each other via, for example, an adhesive layer (preferably using an active energy ray-curable adhesive).

[0084] Although not shown, in practice, a release liner is attached to the surface of the pressure-sensitive adhesive layer 40. The release liner can be temporarily attached until the polarizing plate is ready for use. By using the release liner, for example, the pressure-sensitive adhesive layer 40 is protected and the polarizing plate can be formed into a roll.

[0085] The polarizing plate may be in a long shape or in a sheet shape. In this specification, "long" refers to an elongated shape in which the length is sufficiently longer than the width, for example, an elongated shape in which the length is 10 times or more, preferably 20 times or more, the width. A long polarizing plate can be wound into a roll.

[0086] D-1.Protective layer The protective layer may be formed of any suitable film that can be used as a protective layer for a polarizing film. Specific examples of materials that serve as the main component of the film include cellulose-based resins such as triacetyl cellulose (TAC), and transparent resins such as polyesters, polyvinyl alcohols, polycarbonates, polyamides, polyimides, polyethersulfones, polysulfones, polystyrenes, and cycloolefins such as polynorbornene, polyolefins, (meth)acrylics, and acetates.

[0087] The polarizing plate is typically disposed on the viewing side of the image display device. Therefore, the protective layer 20 may be subjected to surface treatment such as hard coat (HC) treatment, anti-reflection treatment, anti-sticking treatment, anti-glare treatment, etc., as needed.

[0088] The thickness of the protective layer is preferably 5 μm to 80 μm, more preferably 10 μm to 40 μm, and even more preferably 10 μm to 30 μm. When the above-mentioned surface treatment is performed, the thickness of the protective layer includes the thickness of the surface treatment layer.

[0089] In one embodiment, the second protective layer disposed between the polarizing film 10 and the retardation layer 30 is preferably optically isotropic. In this specification, "optically isotropic" means that the in-plane retardation Re(550) is 0 nm to 10 nm and the retardation in the thickness direction Rth(550) is -10 nm to +10 nm.

[0090] In one embodiment, the resin substrate can be used as it is as the protective layer of the polarizing film. According to such a form, the manufacturing process can be reduced.

[0091] D-2. Retardation layer As described above, the retardation layer 30 may be a single layer or may have a laminated structure (for example, a two-layer structure).

[0092] The retardation layer 30 can have any appropriate optical properties according to the application and the like. In one embodiment, the retardation layer 30 includes a first retardation layer that can function as a λ / 4 plate. The first retardation layer typically exhibits a refractive index characteristic of nx>ny=nz. The in-plane retardation Re(550) of the retardation layer is preferably 100 nm to 190 nm, more preferably 110 nm to 170 nm, and even more preferably 120 nm to 160 nm. Here, "ny=nz" includes not only the case where ny and nz are exactly equal but also the case where they are substantially equal. Therefore, within a range that does not impair the effects of the present invention, ny>nz or ny<nz may occur.

[0093] The Nz coefficient of the first retardation layer is preferably 0.9 to 1.5, more preferably 0.9 to 1.3. The first retardation layer may exhibit an inverse dispersion wavelength characteristic in which the retardation value increases according to the wavelength of the measurement light. In this case, Re(450) / Re(550) of the retardation layer is preferably 0.8 or more and less than 1, more preferably 0.8 or more and 0.95 or less.

[0094] The retardation layer 30 can be composed of any appropriate material as long as it can satisfy the desired properties. Specifically, the retardation layer may be a resin film (stretched film), an alignment curing layer of a liquid crystal compound, or a combination thereof.

[0095] D-3. Adhesive layer The adhesive layer 40 may have any suitable structure. Specific examples include acrylic adhesives, rubber adhesives, silicone adhesives, polyester adhesives, urethane adhesives, epoxy adhesives, and polyether adhesives. By adjusting the type, number, combination, and compounding ratio of monomers forming the base resin of the adhesive, as well as the amount of crosslinking agent, reaction temperature, reaction time, and the like, it is possible to prepare an adhesive having desired properties according to the purpose. The base resin of the adhesive may be used alone or in combination of two or more types. The base resin is preferably an acrylic resin (specifically, the adhesive layer is preferably composed of an acrylic adhesive). The thickness of the adhesive layer 40 is, for example, 10 μm to 20 μm.

[0096] D-4. Preparation of polarizing plates A polarizing plate can typically be obtained by laminating various layers such as a retardation layer on the polarizing film obtained through the first and second steps. [Example]

[0097] The present invention will be described in detail below with reference to examples, but the present invention is not limited to these examples. The thickness and moisture content of the resin film are values ​​measured by the following measurement methods. Unless otherwise specified, "parts" and "%" in the examples and comparative examples are by weight. 1. Thickness Thicknesses of 10 μm or less were measured using a scanning electron microscope (manufactured by JEOL Ltd., product name "JSM-7100F"), and thicknesses of more than 10 μm were measured using a digital micrometer (manufactured by Anritsu Corporation, product name "KC-351C"). 2. Moisture content of resin film The resin film alone (resin film peeled from the resin substrate) was dried at 120°C for 2 hours, and the amount of water contained in the resin film was determined by measuring the weight change before and after drying, and the moisture content was calculated.

[0098] [Example 1] (Resin film production) The thermoplastic resin substrate was a long, amorphous isophthalic copolymerized polyethylene terephthalate film (thickness: 100 μm) with a water absorption rate of 0.75% and a Tg of approximately 75° C. One side of the resin substrate was subjected to a corona treatment. A PVA aqueous solution (coating solution) was prepared by adding 13 parts by weight of potassium iodide to 100 parts by weight of a PVA-based resin prepared by mixing polyvinyl alcohol (polymerization degree 4200, saponification degree 99.2 mol%) and acetoacetyl-modified PVA (manufactured by Nippon Synthetic Chemical Industry Co., Ltd., trade name "GOHSEFFIMER Z410") in a ratio of 9:1. The above PVA aqueous solution was applied to the corona treated surface of the resin substrate and dried at 60° C. to form a PVA resin layer with a thickness of 13 μm, thereby producing a laminate. The resulting laminate was uniaxially stretched at its free end to 2.4 times its original size in the machine direction (longitudinal direction) between rolls with different peripheral speeds in an oven at 130°C (auxiliary in-air stretching). Next, the laminate was immersed in an insolubilizing bath (a boric acid aqueous solution obtained by mixing 4 parts by weight of boric acid with 100 parts by weight of water) at a liquid temperature of 40°C for 30 seconds (insolubilizing treatment). Next, the sample was immersed in a dye bath (an aqueous iodine solution obtained by mixing iodine and potassium iodide in a weight ratio of 1:7 with 100 parts by weight of water) at a liquid temperature of 30°C for 60 seconds while adjusting the concentration so that the single transmittance (Ts) of the resulting resin film would be 43% or more (dyeing). Next, the sample was immersed in a crosslinking bath (a boric acid aqueous solution obtained by blending 3 parts by weight of potassium iodide and 5 parts by weight of boric acid with 100 parts by weight of water) at a liquid temperature of 40°C for 30 seconds (crosslinking treatment). The laminate was then immersed in an aqueous boric acid solution (boric acid concentration: 4.0 wt%) at a liquid temperature of 64°C and uniaxially stretched in the longitudinal direction (longitudinal direction) between rolls with different peripheral speeds to a total stretch ratio of 5.5 times (underwater stretching). Thereafter, the laminate was immersed in a cleaning bath (aqueous solution obtained by mixing 4 parts by weight of potassium iodide with 100 parts by weight of water) at a liquid temperature of 20°C (cleaning). Thereafter, while drying in an oven maintained at 90°C, the laminate was brought into contact with a SUS heated roll whose surface temperature was maintained at 75°C for approximately 2 seconds (drying). The shrinkage rate in the width direction of the laminate due to the drying shrinkage treatment was 5.2%. In this way, a resin film having a thickness of 5.5 μm and a moisture content of 4.4% was formed on the resin substrate.

[0099] Next, a 27 μm thick HC-cycloolefin resin (COP) film was attached to one side of the obtained resin film (the side not having the resin substrate) via a UV-curable adhesive, and then the resin substrate was peeled off from the resin film to obtain a laminate of the HC-COP film and the resin film. The HC-COP film was a film in which an HC layer (2 μm thick) was formed on a cycloolefin resin (COP) film (25 μm thick), and the COP film was attached so that it faced the resin film. The resulting laminate was immersed for 5 minutes in a first liquid (aqueous solution) containing 3% boric acid and 0.005% iodine at 71°C, then immersed for 15 seconds in a water bath (second liquid) at room temperature, and dried at 60°C for 1 minute to obtain a polarizing plate having an HC-COP film and a polarizing film.

[0100] [Example 2] A polarizing plate having an HC-COP film and a polarizing film was obtained in the same manner as in Example 1, except that the first liquid was an aqueous solution having a boric acid concentration of 3% and an iodine concentration of 0.0025% at 70°C, and the immersion time in the first liquid was 15 minutes.

[0101] [Example 3] A polarizing plate having an HC-COP film and a polarizing film was obtained in the same manner as in Example 1, except that the first liquid was an aqueous solution having a boric acid concentration of 4% and an iodine concentration of 0.005% at 70°C, and the immersion time in the first liquid was 15 minutes.

[0102] [Example 4] A polarizing plate having an HC-COP film and a polarizing film was obtained in the same manner as in Example 1, except that the first liquid used was an aqueous solution having a boric acid concentration of 4% and an iodine concentration of 0.0025% at 70°C, and the immersion time in the first liquid was 15 minutes.

[0103] [Example 5] A polarizing plate having an HC-COP film and a polarizing film was obtained in the same manner as in Example 1, except that the first liquid was an aqueous solution having a boric acid concentration of 5% and an iodine concentration of 0.01% at 81°C, and the immersion time in the first liquid was 10 minutes.

[0104] [Example 6] A polarizing plate having an HC-COP film and a polarizing film was obtained in the same manner as in Example 1, except that the first liquid was an aqueous solution having a boric acid concentration of 5% and an iodine concentration of 0.005% at 70°C, and the immersion time in the first liquid was 15 minutes.

[0105] [Example 7] A polarizing plate having an HC-COP film and a polarizing film was obtained in the same manner as in Example 1, except that the first liquid was an aqueous solution having a boric acid concentration of 5% and an iodine concentration of 0.005% at 80°C, and the immersion time in the first liquid was 10 minutes.

[0106] [Example 8] A polarizing plate having an HC-COP film and a polarizing film was obtained in the same manner as in Example 1, except that the first liquid was an aqueous solution with a boric acid concentration of 5% and an iodine concentration of 0.005% at 85°C, the immersion time in the first liquid was 10 minutes, and the second liquid was an aqueous potassium iodide solution (concentration 1.2%).

[0107] [Example 9] A polarizing plate having an HC-COP film and a polarizing film was obtained in the same manner as in Example 1, except that the first liquid was an aqueous solution with a boric acid concentration of 5% and an iodine concentration of 0.005% at 85°C, the immersion time in the first liquid was 7 minutes, and the second liquid was an aqueous potassium iodide solution (concentration 2.5%).

[0108] [Example 10] A polarizing plate having an HC-COP film and a polarizing film was obtained in the same manner as in Example 1, except that the first liquid used was an aqueous solution having a boric acid concentration of 5% and an iodine concentration of 0.0025% at 70°C, and the immersion time in the first liquid was 15 minutes.

[0109] [Example 11] A polarizing plate having an HC-COP film and a polarizing film was obtained in the same manner as in Example 1, except that the first liquid used was an aqueous solution having a boric acid concentration of 5% and an iodine concentration of 0.0025% at 60°C, and the immersion time in the first liquid was 30 minutes.

[0110] [Example 12] A polarizing plate having an HC-COP film and a polarizing film was obtained in the same manner as in Example 1, except that the first liquid was an aqueous solution with a boric acid concentration of 5% and an iodine concentration of 0.0025% at 60°C, the immersion time in the first liquid was 45 minutes, and the second liquid was an aqueous potassium iodide solution (concentration 2%).

[0111] [Example 13] A polarizing plate having an HC-COP film and a polarizing film was obtained in the same manner as in Example 1, except that the first liquid used was an aqueous solution having a boric acid concentration of 8% and an iodine concentration of 0.01% at 80°C, and the immersion time in the first liquid was 10 minutes.

[0112] [Example 14] A polarizing plate having an HC-COP film and a polarizing film was obtained in the same manner as in Example 1, except that the first liquid was an aqueous solution with a boric acid concentration of 8% and an iodine concentration of 0.01% at 90°C, the immersion time in the first liquid was 10 minutes, and the second liquid was an aqueous potassium iodide solution (concentration 2%).

[0113] [Example 15] A polarizing plate having an HC-COP film and a polarizing film was obtained in the same manner as in Example 1, except that the first liquid used was an aqueous solution having a boric acid concentration of 8% and an iodine concentration of 0.003% at 80°C, and the immersion time in the first liquid was 10 minutes.

[0114] [Example 16] A polarizing plate having a resin substrate and a polarizing film was obtained in the same manner as in Example 1, except that the laminate (with a resin film formed on the resin substrate) was immersed in the first liquid, the first liquid was an aqueous solution having a boric acid concentration of 4% and an iodine concentration of 0.0025% at 70°C, and the immersion time in the first liquid was 5 minutes.

[0115] [Example 17] A polarizing plate having a resin substrate and a polarizing film was obtained in the same manner as in Example 1, except that the laminate (with a resin film formed on the resin substrate) was immersed in the first liquid, the first liquid was an aqueous solution having a boric acid concentration of 4% and an iodine concentration of 0.0025% at 70°C, and the immersion time in the first liquid was 10 minutes.

[0116] [Comparative Example 1] A polarizing plate having an HC-COP film and a polarizing film was obtained in the same manner as in Example 1, except that the treatment using the first liquid and the second liquid was not carried out.

[0117] Comparative Example 2 A polarizing plate having an HC-COP film and a polarizing film was obtained in the same manner as in Example 1, except that 50°C water was used as the first liquid, the immersion time in the first liquid was 10 minutes, and no treatment using the second liquid was performed.

[0118] Comparative Example 3 A polarizing plate having an HC-COP film and a polarizing film was obtained in the same manner as in Example 1, except that a 70°C aqueous solution (containing no iodine) with a boric acid concentration of 5% was used as the first liquid and the immersion time in the first liquid was 5 minutes.

[0119] Comparative Example 4 A polarizing plate having an HC-COP film and a polarizing film was obtained in the same manner as in Example 1, except that the first liquid was an aqueous solution having a boric acid concentration of 4% and an iodine concentration of 0.003% at 50°C, and the immersion time in the first liquid was 30 minutes.

[0120] Comparative Example 5 A polarizing plate having an HC-COP film and a polarizing film was obtained in the same manner as in Comparative Example 1, except that the dyeing conditions were adjusted.

[0121] [Reference example 1] (Resin film production) A long roll of 30 μm thick PVA resin film (manufactured by Kuraray, product name "PE3000") was uniaxially stretched in the longitudinal direction at 66°C using a roll stretching machine so that the total stretching ratio was 6.5 times, while simultaneously undergoing swelling, dyeing, crosslinking, and washing processes, and finally drying to produce a resin film with a thickness of 12 μm and a moisture content of 11%. The swelling treatment involved stretching while treating with pure water at 20°C. Next, the dyeing treatment involved stretching while treating in a 30°C aqueous solution containing iodine and potassium iodide at a weight ratio of 1:7, with the iodine concentration adjusted so that the resulting resin film had a single-piece transmittance of 42% or higher. Next, a two-stage crosslinking treatment was employed. In the first stage, stretching was performed while treating in a 40°C aqueous solution containing boric acid and potassium iodide. The boric acid content of the aqueous solution used in the first stage was 5.0 wt % and the potassium iodide content was 3.0 wt %. In the second stage, stretching was performed while treating in a 65°C aqueous solution containing boric acid and potassium iodide. The boric acid content of the aqueous solution used in the second stage was 4.3 wt % and the potassium iodide content was 5.0 wt %. Next, washing was performed with a 20°C aqueous solution of potassium iodide. The potassium iodide content of the aqueous solution used for the washing treatment was 2.6 wt %. Finally, the resin film was obtained by drying at 70°C for 5 minutes.

[0122] A 27 μm thick HC-COP film was attached to one side of the obtained resin film via an ultraviolet-curable adhesive to obtain a laminate (polarizing plate) of the HC-COP film and the resin film.

[0123] [Reference example 2] The laminate of Reference Example 1 was immersed in a first liquid (aqueous solution) containing 6% boric acid and 0.003% iodine for 20 minutes at 80° C. Thereafter, it was immersed in a water bath (second liquid) at room temperature for 15 seconds, and then dried at 60° C. for 1 minute to obtain a polarizing plate having an HC-COP film and a polarizing film.

[0124] [Reference example 3] A polarizing plate having an HC-COP film and a polarizing film was obtained in the same manner as in Reference Example 2, except that the temperature of the first liquid was 75°C and the immersion time in the first liquid was 30 minutes.

[0125] [Reference example 4] A polarizing plate having an HC-COP film and a polarizing film was obtained in the same manner as in Reference Example 2, except that the boric acid concentration of the first liquid was 8% and the immersion time in the first liquid was 30 minutes.

[0126] [Reference example 5] A polarizing plate having an HC-COP film and a polarizing film was obtained in the same manner as in Reference Example 1, except that the dyeing conditions were adjusted.

[0127] The following evaluations were carried out for the Examples, Comparative Examples, and Reference Examples. The evaluation results are summarized in Table 1. Representative figures for the evaluation of Appearance 1 below (evaluation results for Comparative Example 5, Example 9, and Example 8) are shown in FIG. 4, and representative figures for the evaluation of Appearance 2 below (evaluation results for Comparative Example 5, Example 9, and Example 8) are shown in FIG. 5. <Evaluation> Single unit transmittance and polarization The polarizing film (polarizing film / HC-COP film) was measured using a UV-visible spectrophotometer (JASCO Corporation, V-7100) to determine the single transmittance Ts, parallel transmittance Tp, and crossed transmittance Tc of the polarizing film. These Ts, Tp, and Tc are Y values ​​measured using a 2-degree visual field (C light source) according to JIS Z8701 and corrected for luminosity. From the obtained Tp and Tc, the degree of polarization P was calculated using the following formula. Polarization degree P(%)={(Tp-Tc) / (Tp+Tc)} 1 / 2 ×100

[0128] Hue (a and b) The polarizing film (polarizing film / HC-COP film) was measured for its individual hue using an ultraviolet-visible spectrophotometer (V-7100, manufactured by JASCO Corporation).

[0129] Appearance 1 The resulting polarizing plate was used to prepare a laminate for evaluation. Specifically, the following retardation layer was attached to the polarizing film side of the polarizing plate via an acrylic adhesive layer (15 μm), and then a reflective sheet (Toray Advanced Film Co., Ltd., "Cerapeel DMS-X42") was attached to the retardation layer via an acrylic adhesive layer (15 μm) to obtain a laminate for evaluation. The reflectance of the reflective sheet measured in SCI mode using a spectrophotometer (Konica Minolta, Inc., "CM-2600d") was 88%. The appearance (presence or absence of streaks) of the obtained evaluation laminate when viewed from the polarizing plate side was visually observed. (Evaluation criteria) Good: No streaks observed Defective: Streaks are observed

[0130] (Preparation of stretched film constituting retardation layer) Polymerization was carried out using a batch polymerization apparatus consisting of two vertical reactors equipped with stirring blades and reflux condensers controlled at 100° C. The polymerization mixture contained 29.60 parts by mass (0.046 mol) of bis[9-(2-phenoxycarbonylethyl)fluoren-9-yl]methane, 29.21 parts by mass (0.200 mol) of isosorbide (ISB), 42.28 parts by mass (0.139 mol) of spiroglycol (SPG), 63.77 parts by mass (0.298 mol) of diphenyl carbonate (DPC), and 1.19 × 10 calcium acetate monohydrate as a catalyst. -2 Part of mass (6.78×10 -5(mol) was charged. After purging the reactor with nitrogen under reduced pressure, heating was performed using a heat transfer medium. Stirring was initiated when the internal temperature reached 100°C. Forty minutes after the start of the temperature increase, the internal temperature reached 220°C. This temperature was maintained while simultaneously reducing the pressure. 90 minutes after reaching 220°C, the pressure was reduced to 13.3 kPa. Phenol vapor by-produced during the polymerization reaction was introduced into a reflux condenser at 100°C, and the small amount of monomer components contained in the phenol vapor was returned to the reactor. Uncondensed phenol vapor was collected by introducing nitrogen into the first reactor and temporarily restoring the pressure to atmospheric pressure. The oligomerized reaction liquid in the first reactor was then transferred to the second reactor. Next, heating and depressurization of the second reactor were initiated, and the internal temperature reached 240°C and the pressure reached 0.2 kPa in 50 minutes. The polymerization was then allowed to proceed until the specified stirring power was reached. When the predetermined power was reached, nitrogen was introduced into the reactor to restore pressure, and the polyester carbonate resin produced was extruded into water, and the strands were cut to obtain pellets.

[0131] The resulting polyester carbonate resin pellets were vacuum-dried at 80°C for 5 hours and then used in a film-making machine equipped with a single-screw extruder (manufactured by Toshiba Machine Co., Ltd., cylinder temperature setting: 250°C), a T-die (width: 200 mm, temperature setting: 250°C), a chill roll (temperature setting: 120-130°C), and a winder to produce a 135 μm-thick long resin film. The resulting long resin film was stretched in the width direction at a stretching temperature of 143°C and a stretch ratio of 2.8 to obtain a 47 μm-thick stretched film. The resulting stretched film had an Re(550) of 143 nm, an Re(450) / Re(550) of 0.86, and an Nz coefficient of 1.12.

[0132] A film exhibiting a refractive index characteristic of nz>nx=ny ("MCP-N(100)", manufactured by Dai Nippon Printing Co., Ltd., Rth(550): -135nm) was bonded to the stretched film obtained above via a UV-curable adhesive (thickness after curing: 1.0 μm) to obtain a laminated film constituting a retardation layer.

[0133] Appearance 2 With an LED backlight (Altek, Topcon Technohouse "SR-UL1R"; luminance measured at a measurement angle of 1.0° and a height of 50 cm; 7200 cd) turned on, a first polarizing plate (Nitto, "SEG1224DUHC"; transmittance 43%), the obtained polarizing plate, and a second polarizing plate (Nitto, "SEG1224DUHC"; transmittance 43%) were placed on top of it in that order, and the appearance (presence or absence of streaks) when viewed from above the second polarizing plate was visually observed. The three polarizing plates were arranged so that the absorption axes of adjacent polarizing plates were perpendicular (three-plate cross method). The first and second polarizing plates were also attached to glass plates. (Evaluation criteria) Good: No streaks observed Defective: Streaks are observed

[0134] [Table 1]

[0135] In the comparative example, streaks were visible along the absorption axis direction (stretching direction) of the polarizing film, but no streaks were visible in the examples. Note that in comparative example 2, which used a first liquid containing no boric acid, it is believed that iodine escaped from areas with weak cross-linking, making streaks more visible. [Industrial Applicability]

[0136] The polarizing film according to the embodiment of the present invention is suitably used in image display devices such as liquid crystal display devices, organic EL display devices, and inorganic EL display devices. [Explanation of symbols]

[0137] 1. Laminate 2 Thermoplastic resin base material 3 Polyvinyl alcohol (PVA) resin layer 10 Polarizing film 20 protective layer 30 Retardation layer 40 adhesive layer 100 Polarizer

Claims

1. contacting a resin film containing iodine and having a moisture content of 15% by weight or less with a first liquid; The first liquid is an aqueous solution of boric acid and iodine, and the temperature of the first liquid is 60° C. or higher. A method for manufacturing a polarizing film.

2. The method according to claim 1 , wherein the resin film brought into contact with the first liquid has a single layer transmittance of 44% or more.

3. The method according to claim 1 , wherein the first liquid has a boric acid concentration of 3% by weight or more.

4. The method according to claim 1, wherein the first liquid has an iodine concentration of 0.002% by weight to 0.01% by weight.

5. The method according to claim 1 , further comprising contacting the resin film, which has been in contact with the first liquid, with a second liquid.

6. The method of claim 5 , wherein the second liquid comprises water.

7. The method according to claim 1 , which produces a polarizing film having a thickness of 22 μm or less.